Race and Reconciliation in Australia - Green, M.; Saggers, Sherry (Sydney, 2007)
Like the children and young people in the vignette above, Indigenous people throughout Australia are making lives for themselves while facing complex challenges, from practical considerations such as trying to stay alive longer and attain a decent standard of living, to questions about their identities and relationships with other Australians. Understanding the position of Indigenous people in contemporary Australia requires some knowledge of the past and the way in which the past continues to influence subsequent generations of people. Race and reconciliation are integral to this understanding. Theories of race, once fixed, have become more complex; invalid biological and ‘science’-based frameworks have been replaced by theories focusing on the multiple social meanings of race and race relations. These have implicitly framed the development of policies addressing Indigenous disadvantage, from the earliest attempts to ‘protect’ Indigenous people by forcing them into missions and reserves, to the current mainstreaming of services and challenges to communal land title. The notion of reconciliation—the bringing together of Indigenous and non-Indigenous Australians—encourages us to think about the practical and symbolic dimensions of the past and present and what is required to address persistent inequality.